The Effectiveness of Task-Based Learning in Teaching Integrated Skills - Aisa Damayanti Kartini; Linda Mayasari; Sofi Yunianti (Tell : Teaching of English Language and Literature Journal, 2020)
Task-Based Learning has proven as a good approach in teaching English. The approach has been implemented in teaching language, especially English integrated skills. This is enough for researcher to do the study about implementation of TBL to training students mastery for language’s macro skills. The material which taken as the topic was natural disaster. Therefore, it was easy to learn for the students as they had experienced the event through their environment. The objective of this research is to find out if TBL effectives in teaching the students about integrated skills and to know how Task-Based Learning improves students’ language abilities. This research uses Classroom Action Research with two cycles. There are several phases in this research design, namely: (a) planning, (b) action, (c) observing and, (d) reflection. The subject is class of XI NKN 2 at vocational high school in Surabaya. Based on this study, it was proven that Task-Based Learning could improve the eleventh grader students’ score which in the good level with 80% students passed the Minimum Mastery Criteria (KKM) after the conduction of cycle 2. This study resulted in Task-Based Learning was able to help students enggage in learning four language skills in the same time while being active during the learning process.